The Effect of Student Readiness and Activeness on Student Learning Achievement - Windy Yuni Triana; Abdillah, Candra; Dameis Surya Anggara (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2024)
This study aims to analyze the magnitude of the influence between learning readiness on student learning achievement; (2) to determine the magnitude of the influence between Student Activeness on student learning achievement; (3) to determine the magnitude of the influence between Learning Readiness and Student Activeness on student learning achievement. The study has a quantitative approach, with an association methodology. The population in this study were all students of class XII TKRO SMK Sasmita Jaya 2 totaling 54 students with a simple random sampling technique with a sample size of 42 students. Data were collected by questionnaire, observation and documentation. The research instruments were in the form of a learning readiness questionnaire sheet, a student antipathy questionnaire sheet, and documentation of student learning achievement. Data were analyzed through inferential statistics in the form of simple linear regression and multiple linear regression. The results of the study were (1) the influence of the learning readiness variable on learning achievement was 0.126 or 12.6% 2) the influence of the student activeness variable on learning achievement was 0.040 or 4%; 3) The influence of the variables of learning readiness and student activity simultaneously on learning achievement is 0.141 or 14.1% and the remaining 85.9% is influenced by other factors.